GO GREEN DALAM KARYA SENI GRAFIS - HANAFI, Drs. Irwan, M. Sn., Yofita Sandra, S>Pd., M.Pd. (Universitas Negeri Padang, 2019)
This final task is aimed to visualize the damage in our environment which is caused by human behavior. The damage is visualized into graphic art by using relief technique print then we callit as go-green. Go green is a term wich point on greening or repairing the damage in environment. Methods in creating this final task is using 4 phases, they are preparation, elaboration, synthesis,and realization concept. Then this creation of go green is started with creating sketsa, preparing tools and materials, process of finishing this work. This final task will be finished with 10 categories: air pollution, water pollution, the remain hope, burnt world, friendly to environment, nature code, dependenceeach other, balance, life foundation, friendly environment. From this final task we expect that people will be more aware and more care to environment and make this as reference to graphic artin the nextime.Kata kunci: Go green, Kerusakan lingkungan, Seni Grafis